EduGame Maru: Application for Early Mathematics Learning as an Alternative for Optimizing Cognitive Ability for 4-6 Years Children - Rr Deni Widjayatri; Lizza Suzanti; Nenden Sundari; Yulianti Fitriani; Rika Ar Nurazka; Firda Rahmadini; Ria Yuliati Ichsan; Nabila Qotrunnida (EduBasic Journal: Jurnal Pendidikan Dasar, 2022)
Mathematics teaching process in kindergarten must adapt to the pandemic situation which require learning from distance. This research develops an Android-based application for learning mathematical concepts, named EduGame Maru, consisting of five types of games: recognizing numbers, algebra, statistics, geometry, and probability. This research aimed to create an interactive, innovative, and practical application as a digital medium. The method used in this research was the RD model, with 4D development (define, design, develop, and disseminate). The EduGame Maru application received a validation result of "very feasible for use," with 3.36 points from media expert validators and 3.64 points from material expert validators, so the average was 3.50. Meanwhile, during the testing at Kindergarten Labschool, Universitas Pendidikan Indonesia, Serang Campus, EduGame Maru application got 3.56 points from the teacher's assessment. In this case, the EduGame Maru application did not only train cognitive abilities but also help children to understand early mathematical concepts by applying the NCTM (National Council of Teachers of Mathematics) principles. Therefore, it can be concluded that EduGame Maru can help teachers and parents optimize the cognitive aspects of children aged 4-6 years, especially early mathematical concepts during online learning.